Design of Solar Powered Cooling Engine For Fishing Vessel - Didit Eko Setiawan; Budhi Hascaryo; Fis Purwangka; Vita Rumanti; Ari Purbayanto; Berbudi Wibowo (International Journal of Marine Engineering Innovation and Research, 2024)
The fishermen in Sendang Biru, Malang, East Java Province, Indonesia, using boat <= 5 GT, specifically an outrigger boat with 10,6 m Length of Overall (LoA), 1,3 m Breadth (B), and 0,7 m Depth (D), have experienced low priced fish catches for many years caused by low quality of fish handling on board. In this research, the researcher overcomes the problem by designing the solar powered cooling engine (SPCE) to maintain the caught fish quality on boat <= 5 GT, especially the boat with outrigger and size as previously mentioned. Meanwhile, the outrigger boat as mentioned above has limited in term of its space and its capacity on board. The research designed the SPCE that fitted to space and capacity of the outrigger boat. The stability of the boat had been analyzed by using IMO resolution on "IMO A.749 (18) Chapter 3". The result of the analyses showed that the SPCE designed met the IMO criteria applicable to all ships, which has GZ Max 0,492 m at 25.5°, and as the general arrangement of the SPCE on the boat, the SPCE device put in the middle of the boat while in the back part of the boat is fisher working area.